Faktor – Faktor yang Mempengaruhi Harga Saham JAKARTA ISLAMIC INDEX (JII) di Bursa Efek Indonesia - Ardhansyah Putra Harahap; Alistraja Dison Silalahi (COSTING : Journal of Economic, Business and Accounting, 2020)
The existence of the capital market in a country's economic activities is an alternative source of funds for companies and also for investors to invest by trading companies that have gone public. This study aims to determine the effect of the combined market capitalization of companies and interest rates on the stock price of the Jakarta Islamic Index (JII) during the 2015-2017 period. The sampling technique used in this study is a purposive sampling method and based on predetermined criteria obtained 31 samples from 36 populations that meet the criteria. Data analysis techniques used in testing the normality of data using Kolmogorov-Smirnov One-Sample, while in testing the hypothesis of this study that is by multiple regression analysis, t test and F test conducted with the help of SPSS software ver. 20. The Results of hypothesis testing shows that both the market capitalization variable and the interest rate have a significant and significant effect on the Jakarta Islamic Index's stock price on the Indonesia Stock Exchange. Keywords: Market Capitalization, Rate, Stock JII